Dampak Kebijakan Merdeka Belajar Kampus Merdeka (MBKM) pada Perguruan Tinggi Swasta - Alfiansyah, Iqnatia (DIDAKTIKA : Jurnal Pemikiran Pendidikan, 2024)
Merdeka Belajar Kampus Merdeka (MBKM) is an independent and versatile higher education learning program designed to create a non-restrictive creative learning community that meets student needs. This research aims to see the impact and perception of implementing Merdeka Belajar Kampus Merdeka (MBKM) for all students in private universities, especially at the Muhammadiyah University of Gresik, Primary School Teacher Education Study Program with the aim of seeing the extent of students’ understanding and perceptions and the impact of implementing the Independent Campus Learning (MBKM) program. This research is descriptive research with a quantitative approach using survey methods. Data was obtained from respondents who were students of the Muhammadiyah Gresik University Primary School Teacher Education Study Program. Data was collected through questionnaires. Data analysis techniques start from data collection and then analyzed using descriptive analysis. The results of this survey research are in the form of answers or responses from students in the elementary school teacher education study program, Faculty of Teacher Training and Education (FKIP) Muhammadiyah University of Gresik to the Merdeka Belajar Kampus Merdeka (MBKM) program.